Enhanced photoresponse of a self-powered gallium nitride photodetector via sequentially-deposited gold nanoparticles for sustainable optoelectronics - TEKER, KAŞİF (My University, 2023)
© 2023, The Minerals, Metals & Materials Society.It is becoming crucial to design/fabricate eco-friendly, sustainable electronic and photonic devices to minimize the carbon footprint for future systems. In this study, we have demonstrated a steady photoresponse enhancement of the self-powered GaN ultraviolet photodetector (GaN-UVPD) via sequentially deposited gold nanoparticles (Au NPs) under 254, 302, and 365 nm UV light exposure. The AuNP-deposited GaN-UVPD exhibited excellent responsivity of 0.65 A/W and detectivity of 6.51 × 1012 cm.Hz1/2 W−1 under 302 nm UV light without any external power. Moreover, the sensitivity of the device increased from 1.98 × 106% to 3.32 × 106% following Au nanoparticle deposition. Additionally, the plausible mechanisms for the self-powered and Au nanoparticle-induced photoresponse enhancement have been discussed. In brief, the high-performance photoresponsivity of our self-powered GaN-UVPD could find many useful applications in sustainable energy and eco-friendly optoelectronic devices.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Temel Bilimler; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Signal Processing; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; FİZİK, YOĞUN MADDE; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATERIALS SCIENCE; PHYSICS; ENGINEERING, ELECTRICAL & ELECTRONIC; MATERIALS SCIENCE, MULTIDISCIPLINARY; PHYSICS, CONDENSED MATTER; Elektronik, Optik ve Manyetik Malzemeler; Fizik Bilimleri; Yoğun Madde Fiziği; Malzeme Kimyası; Elektrik ve Elektronik Mühendisliği; Electronic, Optical and Magnetic Materials; Physical Sciences; Condensed Matter Physics; Materials Chemistry; Electrical and Electronic Engineering; Au nanoparticles; GaN-UVPD; plasmonics; Self-powered photodetectors; sustainable energy